NESH Regulates Dendritic Spine Morphology and Synapse Formation - Bae, Jeomil (Public Library of Science, 2012)
BACKGROUND: Dendritic spines are small membranous protrusions on the neuronal dendrites that receive synaptic input from axon terminals. Despite their importance for integrating the enormous information flow in the brain, the molecular mechanisms regulating spine morphogenesis are not well understood. NESH/Abi-3 is a member of the Abl interactor (Abi) protein family, and its overexpression is known to reduce cell motility and tumor metastasis. NESH is prominently expressed in the brain, but its function there remains unknown. METHODOLOGY/PRINCIPAL FINDINGS: NESH was strongly expressed in the hippocampus and moderately expressed in the cerebral cortex, cerebellum and striatum, where it co-localized with the postsynaptic proteins PSD95, SPIN90 and F-actin in dendritic spines. Overexpression of NESH reduced numbers of mushroom-type spines and synapse density but increased thin, filopodia-like spines and had no effect on spine density. siRNA knockdown of NESH also reduced mushroom spine numbers and inhibited synapse formation but it increased spine density. The N-terminal region of NESH co-sedimented with filamentous actin (F-actin), which is an essential component of dendritic spines, suggesting this interaction is important for the maturation of dendritic spines. CONCLUSIONS/SIGNIFICANCE: NESH is a novel F-actin binding protein that likely plays important roles in the regulation of dendritic spine morphogenesis and synapse formation.